Implementation Of The Weighted Product (Wp) Method In Selecting The Best Pesticide (Case Study: Kud Subur Makmur Village Teluk Panji Iv) - Sulistiani, Nur; Hutagalung, Fatma Sari (Bahasa Indonesia, 2024)
Pesticides are materials that are widely used in various sectors, especially in agriculture, plantations, forestry, fisheries, and food agriculture. The use of pesticides in the agricultural sector aims to eliminate nuisance plants, fungi, insects, rodents, and other organisms so that it has an impact on increasing agricultural production. This study aims to apply the Weighted Product (WP) method in determining the best pesticide in KUD Subur Makmur, Teluk Panji IV Village. The Weighted Product method is used because of its ability to handle many criteria relevant to the selection of pesticides, such as price, package size, type of pest eradicated and durability. Data was collected through an interview with one of the employees as well as through literature study and document analysis related to available pesticides. Each criterion is then given a weight according to its level of importance based on the results of the interview. The results show that the Weighted Product method is effective in providing optimal pesticide selection according to local needs and conditions. The implementation of this method can help in making better decisions regarding the use of pesticides, so as to increase agricultural productivity and sustainability. The impact obtained from this research is that it can increase crop yields in a sustainable manner and reduce losses due to ineffective or harmful pesticide use.